Transformation of primary murine peritoneal mast cells by constitutive KIT activation is accompanied by loss of Cdkn2a/Arf expression - Capellmann, Sandro; Sonntag, Roland; Schüler, Herdit; Meurer, Steffen K.; Gan, Lin; Kauffmann, Marlies; Horn, Katharina; Königs-Werner, Hiltrud; Weiskirchen, Ralf; Liedtke, Christian; Huber, Michael (Frontiers in Immunology, 2023)
Mast cells (MCs) are immune cells of the myeloid lineage distributed in tissues throughout the body. Phenotypically, they are a heterogeneous group characterized by different protease repertoires stored in secretory granules and differential presence of receptors. To adequately address aspects of MC biology either primary MCs isolated from human or mouse tissue or different human MC lines, like HMC-1.1 and -1.2, or rodent MC lines like L138.8A or RBL-2H3 are frequently used. Nevertheless, cellular systems to study MC functions are very limited. We have generated a murine connective tissue-like MC line, termed PMC-306, derived from primary peritoneal MCs (PMCs), which spontaneously transformed. We analyzed PMC-306 cells regarding MC surface receptor expression, effector functions and respective signaling pathways, and found that the cells reacted very similar to primary wildtype (WT) PMCs. In this regard, stimulation with MAS-related G-protein-coupled receptor member B2 (MRGPRB2) ligands induced respective signaling and effector functions. Furthermore, PMC-306 cells revealed significantly accelerated cell cycle progression, which however was still dependent on IL-3 and stem cell factor (SCF). Phenotypically, PMC-306 cells adopted an immature connective tissue-like MCs appearance. The reason for immortalization most likely is the loss of the two critical cell cycle regulators Cdkn2a/INK4A and Arf/p19, respectively. The loss of Cdkn2a and Arf expression could be mimicked in primary bone marrow-derived mast cells (BMMCs) by SCF supplementation strongly arguing for an involvement of KIT activation in the transformation process. Hence, this new cell line might be a useful tool to study further aspects of PMC function and to address tumorigenic processes associated with MC leukemia.